Specialty native rice (Oryza sativa L.) germplasm of Uttara Kannada, India - Bhat, R.S.=700 1 Gowda, M.V.C.
(En, Fr, Es)
ilus., 6 ref.
Keywords: ORYZA SATIVA; VARIACION GENETICA; CONSERVACION DEL GERMOPLASMA; ITALIA